The role of deprivation and alcohol availability in shaping trends in violent crime - Lightowlers, Carly (European journal of criminology, 2023)
It is well known that both deprivation and alcohol availability are associated with violent crime. However, less is known about whether the former moderates the latter. Pioneering the linkage of novel alcohol availability measures derived from consumer data with police data and an index of deprivation, we examine inequalities in violent crime across small-level geography (LSOAs) for the whole of England. Our findings confirmed a recent upward trend in recorded violent crime in England between 2011 and 2018 and substantial between-area variability in recorded violent crime, as well as an increase in violent crime inequality across LSOAs during the period of analysis. Violent crime was higher in areas with increased deprivation and alcohol availability, especially in the form of on-licensed premises. On-licence availability, in the form of pubs, bars and nightclubs, explained variability in recorded violent crime more so when compared with off-licence availability. A positive interaction effect between alcohol availability (in the form of on-licensed premises) and deprivation showed how deprivation amplified the impact of alcohol availability, with more deprived areas having a stronger impact of on-licence availability on violent crime. Deprivation is thus an important contextual factor when considering rates and the social ecology of violence. Our findings suggest a need to respond to the disproportionate impact of violence on areas with higher levels of deprivation and availability of on-licensed premises.